Ca2+ and Ca2+-interlocked Membrane Guanylate Cyclase Modulation - Rameshwar K Sharma (Frontiers Research Topics, 2015)
The tale of cyclic GMP has been astonishing. Having overcome an initial disbelief, cyclic GMP has risen to its present eminence as a premium cellular signal transduction messenger of not only hormonal extracellular but also of the intracellular signals. This research topic focuses on the pathways and functions of membrane guanylate cyclases in different tissues of the body and their interplay with intracellular sensory signals where in many cases, cyclic GMP along with Ca2+ have taken on roles as synarchic co-messengers.